Turbulence and interactions proceedings of the ti 2018 conference, june 25-29, 2018, les trois-ilets, martinique, france - Deville, Michel; Calvin, Christophe; Couaillier, Vincent; Plata, Marta De La Llave; stivalèzes, Jean-Luc E; Lê, Thiên Hiêp; Vincent, Stéphane (Springer, 2021)
This book presents a snapshot of the state-of-art in the field of turbulence modeling, with an emphasis on numerical methods. Topics include direct numerical simulations, large eddy simulations, compressible turbulence, coherent structures, two-phase flow simulation and many more. It includes both theoretical contributions and experimental works, as well as chapters derived from keynote lectures, presented at the fifth Turbulence and Interactions Conference (TI 2018), which was held on June 25-29 in Martinique, France. This multifaceted collection, which reflects the conference´s emphasis on the interplay of theory, experiments and computing in the process of understanding and predicting the physics of complex flows and solving related engineering problems, offers a timely guide for students, researchers and professionals in the field of applied computational fluid dynamics, turbulence modeling and related areas.